Utilisation of cervical cancer screening among women living with HIV at Kenya's national referral hospital - James M. Kangethe; Aliza Monroe-Wise; Peter N. Muiruri; James G. Komu; Kenneth K. Mutai; Mirriam M. Nzivo; Jillian Pintye (AOSIS, 2022)
Background: In 2009, Kenyatta National Hospital (KNH) integrated cervical cancer screening within HIV care using visual inspection with acetic acid (VIA) and Pap smear cytology. Objectives: We evaluated utilisation of cervical cancer screening and human papillomavirus (HPV) vaccination among women living with HIV (WLHIV) receiving HIV care at KNH. Method: From November 2019 to February 2020, WLHIV aged ≥ 14 years were invited to participate in a survey following receipt of routine HIV services. We assessed awareness of cervical cancer, uptake of cervical cancer screening, uptake of the HPV vaccine, and barriers to utilisation of these services. In a subset of survey participants, focus group discussions (FGDs) were also conducted to identify screening barriers. Results: Overall, 305 WLHIV participated in the survey. Median age was 36 years (interquartile range [IQR]: 28-43), 41% were married, and 38% completed secondary education. Most (90%) had HIV RNA 1000 copies/mL. Awareness of cervical cancer was high (84%), although only 45% of WLHIV had screened for cervical cancer at the referral hospital and only 13% knew how to prevent high-risk HPV. No participants had received an HPV vaccination. Older age, higher education, and knowledge of the HPV vaccine were associated with higher likelihood of cervical cancer screening (P  0.05). In FGDs, barriers to utilising the services included user fees, fear of the procedure impacting fertility, age and gender of the provider, and long waiting times. Conclusion: Despite integration with HIV services, the utilisation of cervical cancer screening was low among WLHIV and implementation barriers contributed to low utilisation.